Nutrient- Growth Regulator Interaction in Snakegourd (Trichosathes anguina L.) under Drip Irrigation System - Elizabeth K Syriak (Department of Agronomy, College of Agriculture, 1998)
Two field experiments were conducted at the Instructional Farm, College of Agriculture, Vellayani, Thiruvananthapuram, to study the effect of varying levels of nitrogen (n), ethephon (g) and drip irrigation frequency (i) on the productivity of snakegourd. The influence of the treatments on the size, quality and shelf life of the produce and also on the physico-chemical properties of soil was investigated. The trials were conducted during the summer seasons (December to April) of 1994-'95 and 1995-'96. The experiments were laid out in 4 2x2 + 2 asymmetrical confounded factorial design with two replications and each replication included two blocks. Combinations of four levels each of N (35, 70, 105 and 140 kg ha'), ethephon (0, 50, 100 and 200 ppm) and two frequencies of drip irrigation (5 mm CPE and 10 mm CPE) constituted the treatments along with two controls (nogoiI and llogoi2) in each block. The highest order interaction NOI was confounded in both the replications. Results of the field experiments revealed that during both the years of experimentation, nitrogen, ethephon and irrigation frequency exerted significant positive influence on the fruit yield of snakegourd. During both the years, the higher